Digital Activism: Covid-19 Effects in Campus Learning - Ridzal Wahid; Florence Pribadi; Berlian Ester Wakas (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The use of the internet is a part of our daily lives. Most of us spend a large part of using quotas on social media applications, such as Facebook, Twitter, Instagram, and YouTube as social media channels . Covid-19 has bridged the rapidly increasing use of social media / internet, the existence of a distance learning system (online) proving that this pandemic has focused on learning shifting from conventional to distance or online (in the network). The writing method uses a qualitative paradigm with a descriptive approach. Discussion 1. Covid-19 Era Digital Activism 2. Covid-19 Effects on Learning Systems 3. Health Effects of Distance or Online Learning Models (in network). Conclusion: COVID-19 spread in Indonesia in early March 2020. The spread of this virus causes losses to many countries, especially in the economic field. In the field of education, COVID-19 also changed the learning model drastically; all learning activities are carried out online starting from elementary school level to university level. Health effects need to be considered in the present, so it is hoped that every social actor understands and overcomes the effects of the use of media in distance learning.